As naturezas nos sonetos de Cláudio Manuel da Costa - Centurión, Pedro Guagliano (2016)
This paper aims to investigate through the poetry analysis the representations Nature has in Cláudio Manuel da Costa. The selected corpus concentrates on twenty-eight of the one hundred sonnets of the volume Obras. To do so a characterization of this time and period poetry is required as also of the time that the author lived in. Both the historical characterizations of the time as of the poetry are essential to understand what elements or representations were pertinent at the time. Considering it we can better perceive the elements to read Cláudio’s poetry. To better understand his style we consulted some literary history works such as Alfredo Bosi (2015), Afrânio Coutinho (2007), Antonio Candido (2014) and José Guilherme Merquior (2014). To describe the classical style some texts were consulted, such as Roland Barthes’ article: Existe uma escrita poética? O grau zero da escrita: seguido de novos ensaios críticos (2004) and Introdução à Poética Clássica de Segismundo Spina (1967). Regarding the Brazillian History context Inconfidência Mineira’s books were used: Kenneth Maxwell (2010), Augusto de Lima Junior (1968) e João Pinto Furtado (2002). The material selected for analysis had two criteria. The first one consist in selecting those sonnets in which the nature is more prominent and the second one is the role nature has on the poem. The analysis concentrates in the nature and its role aiming the kind of representation it has: according to the bucolic genre, if the nature has a passive role or an active one, if it has human traces, etc